Women characters in selected women folktales - Maponya, Maphuti Lydia (My University, 2018)
Women characters in selected Sepedi folktales, seeks to reveal that the Sepedi folktales are set in the patriarchal structures. They use ogres, giants and man-like creatures to achieve their pleasures and ends in the face of social and cultural confines. These creatures are used to create social distance for contemplating acts and ideas that otherwise might appear to be intolerably disturbing. They evoke a sense of shock, awe and fear among women. These folktales are thus appropriate to some of the evils attributed to women in particular. Women are portrayed in the thesis as vulnerable and marginalised. Their characters vacillate from disobedience, stupidity, mischievousness, weak, untrust-worthy and wizardry. According to this kind of thought, they are reduced by the society to be indecisive. The researcher’s point of view reveals that not all women are weak and submissive, as some are brave, intelligent, trustworthy, obedient and tactful. Most of the women play important roles in the society. The ogres and fearful creatures, even if they perform evil tactics, women in many cases seem to outmanoeuvre the brutality of the enemy. Finally, through the use of feminism, the study tackles the struggle of women in a folktale environment with a view to understand human lives.
Thesis (Ph.D. (Folklore Studies)) -- University of Limpopo, 2018
Keywords: Women characters; Folktales; Folklore -- South Africa; Tales; Women in literature